Risky sexual behaviour amidst predicament of acceptable sexually transmitted infection partner notification modalities: A cross-sectional survey amongst minibus taxi drivers in Gauteng Province, South Africa - Mathildah M. Mokgatle; Sphiwe Madiba (South African Family Practice)
Background: Sexually transmitted infection patient-initiated partner notification (PN) approach has been implemented over a decade in South Africa, however, use and update by patients has been limited. This study assessed the perceived use of patient-initiated PN by using referral slips and measured the level of acceptability of provider-initiated PN by using short message service (SMS) to the personal mobile phones of sexual partners.